Strategi Akselerasi Pengembangan Invensi untuk Meningkatkan Daya Saing Kabupaten Semarang - Angela Merici Wahyuningtyas (Media Informasi Penelitian Kabupaten Semarang, 2025)
Innovation is an acceleration of achieving development goals in the form of technology, methods, approaches and new business models as improvements to previous conditions so as to increase regional competitiveness. This study aims to identify the strategies that can be implemented by Semarang Regency to increase regional competitiveness that can be generated from its innovation acceleration efforts. The research method used is a qualitative descriptive method equipped with a SWOT analysis and strategies that must be carried out. From the results of the analysis, it is concluded that Semarang Regency has the opportunity to have strong competitiveness if innovation acceleration is carried out while simultaneously reducing obstacles and challenges. Strategies that can be used to support strengthening innovation acceleration include strengthening the capacity of innovative human resources, collaboration between stakeholders and expanding networks to the global market and establishing knowledge transfer to continue to make improvements and support continuous innovation.